The Adoption of Electronic Data Interchange (EDI) among Small-Medium-Enterprises (SMEs) in Klang valley / Norul Izza Salahuddin - Salahuddin, Norul Izza (2007)
Nowadays, the adoption of information technology (IT) in business operations is no longer privilege to large organizations only. Small-Medium-Enterprises also have adopted the IT in process of gaining the benefits of using it. However, there has been little research conducted and published on the adoption of Electronic Data Interchange among SMEs in Malaysia. Most previous researches were done in the context of Europe, United State and Australia. This study is handled in order to identify the influences factors of EDI adoption decision among SMEs in Malaysia especially for Klang Valley region and then provide recommendations regarding the adoption decision. For gaining data, researcher used the method of distributing questionnaire and handled some phone interviews. For the analyses and findings, researcher used the SPSS software. Methods that are used in this software are; descriptive, Cronbach’s Alpha of reliability and Coefficient Correlation Test. The findings indicate that the most influences factors that contribute to the EDI adoption decision among SMEs are the cost factor. Then, it being followed by the top management support factor, personnel factor, data confidentiality factor and lastly, total time implementation factor. Based on these findings, recommendations regarding EDI adoption decision among SMEs in Klang Valley are provided.